Narasi Deradikalisasi Muslimah Bercadar dalam Akun @niqabsquad_official - Khoirin Nisai Shalihati (Islamic Management and Empowerment Journal, 2019)
The use of veils for Muslim women is still menui pros and cons. The existence of different attitudes is in accordance with the beliefs, values and knowledge of religious beliefs. This study aims to explain the radicalization narratives that have weakened veiled Muslim women by building a more interesting and conceptual comparative narrative, namely, the narrative of de-radicalization. This study uses an ethnographic approach by analyzing the comments column of various parties who argue. The results showed that veiled Muslim women affiliated in @niqabsquad_official were not terrorists, not terrorist wives and not radical Islamists. The @niqabsquad_official account becomes a virtual veiled Muslim group oriented to Mulimah's hijrah concerning obedience to her religion. Each column of comments was filled with opinions and motivations of deradicalization which did not corner a particular religion.